The Development of the Approach of Discipline-Based Art Education and Its Influence on the Field of Art Education - Yousef Ibrahim Alamoud (Journal of Islamic Studies, 2003)
This research deals with discipline-based art education as one of the most important modem approaches in the fie rd of art education. Major research objectives are: to define the concept of this approach, to show its historical eVol.ution, and to illustrate its importance and role in the introduction of new concepts, which contributed to major advancements in the field of art education during the final quarter of the last century. To achieve these objectives, historical methodology was implemented. The procedures were to follow these developments, concentrate on theoretical contributions of major scholars, and identify many art programs, projects, centers, places and times which represent the landmarks of these developments. Events were classified and interpreted according to the is historical sequence. The research reached some conclusions regarding the crucial points in the approach historical developments, its defining qualities, and its major impact on curriculum, teachers, students, assessment, and technology. Finally, the researcher recommended that this approach can be introduced to the theory of Saudi art education through teaching, publishing and translating its major theoretical foundations. In addition, communication and cooperation between the Getty Education institute for the Arts and Saudi art education specialists can be established and supported to further develop better understanding for possible application of this approach in Saudi schools.